The comprehensive understanding of 10 mA cm(geo)−2 as an evaluation parameter for electrochemical water splitting - Wei, Chao (2020)
Comparing the overpotential required to reach the current density of 10mA cm(geo)-2 (per geometric area of an electrode) (η@10mA cm(geo)-2) is a popular method of ranking electrocatalysts for water-splitting reactions, i.e., the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER).However, such methodology is, in essence, not reasonable for studying the intrinsic chemistry difference of electrocatalysts. To have a rational understanding of η@ 10 mA cm(geo)-2, here, its historical origin and its limitations on reﬂecting the intrinsic electrocatalytic activity are discussed. The η@10mA cm(geo)-2 is a valid practical parameter to assess water-splitting devices, but it cannot determine whether a particular electrocatalyst is intrinsically active or not.